Investigation of the Effects of Anisotropic Flow of Pore Water and Multilayered Soils on Three-Dimensional Consolidation Characteristics - Arpan Laskar; Sujit Kumar Pal (Advances in Materials Science and Engineering)
Many practical engineering problems are seriously different from the assumptions which are considered for one-dimensional consolidation test and need to concentrate on three-dimensional consolidation of soil under different boundary conditions. In this study three-dimensional consolidation tests are performed with four different anisotropic flow conditions of pore water and fifteen different combinations of horizontal layered soils. Twelve different three-dimensional consolidation tests are also performed with different soils, surrounded by anisotropic vertical soil layers on two opposite sides. From these studies, it is observed that the anisotropic flow of pore water does not have any effect on initial and final surface settlement of soil but has a significant effect during the consolidation process. The anisotropic flow of pore water during the consolidation process has an immense effect on the coefficient of consolidation. Horizontal layered soil has a great effect on both surface settlement and the rate of settlement. Vertical soil layers on two opposite sides of consolidative soil have an immense effect on the horizontal movements of consolidating soil, finally affecting the resultant vertical settlement of soil. Vertical anisotropic surrounding soil layers also have an effect on the rate of consolidation settlement.